Penyelesaian Ganti Kerugian Pada Nasabah Bagi Nasabah Yang Dirugikan Akibat Kesalahan Sistem Bank Pada Layanan Mobile Banking - Arsyad, Melinda; Thalib, Mutia CH.; Kamba, Sri Nanang Meiske (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
Abstract Mobile banking is an electronic channel facility that can be accessed by customers who use mobile banking by using smartphones (which have their mobile banking applications activated). there are technical errors and/or human errors that result in losses for customers who use mobile banking.This thesis research is entitled Settlement of compensation for customers who use mobile banking who experience transaction errors.This research discusses first, how the legal provisions of the Banking Law in making mobile banking.Second, customer legal protection in the event of human error and technical error in the use of mobile banking and lastly the implementation of compensation for customers who experience mobile banking transaction errors.The research used in writing this thesis is a normative juridical research method. The results of the study show that the settlement of compensation provided by the bank to customers who experience transaction errors is equivalent to the material losses experienced by the customers who use the mobile banking.